Therapeutic Potential of Quercetin to Alleviate Endothelial Dysfunction in Age-Related Cardiovascular Diseases - Dagher, Olina; Mury, Pauline; Thorin-Trescases, Nathalie; Noly, Pierre Emmanuel; Thorin, Eric; Carrier, Michel (Frontiers in Cardiovascular Medicine, 2021)
The vascular endothelium occupies a catalogue of functions that contribute to the homeostasis of the cardiovascular system. It is a physically active barrier between circulating blood and tissue, a regulator of the vascular tone, a biochemical processor and a modulator of coagulation, inflammation and immunity. Given these essential roles, it comes to no surprise that endothelial dysfunction is prodromal to chronic age-related diseases of the heart and arteries, globally termed cardiovascular diseases (CVD). An example would be ischemic heart disease (IHD), which is the main cause of death from CVD. We have made phenomenal advances in treating CVD, but the aging endothelium, as it senesces, always seems to out-run the benefits of medical and surgical therapies. Remarkably, many epidemiological studies have detected a correlation between a flavonoid-rich diet and a lower incidence of mortality from CVD. Quercetin, a member of the flavonoid class, is a natural compound ubiquitously found in various food sources such as fruits, vegetables, seeds, nuts and wine. It has been reported to have a wide range of health promoting effects and has gained significant attention over the years. A growing body of evidence suggests quercetin could lower the risk of IHD by mitigating endothelial dysfunction and its risk factors, such as hypertension, atherosclerosis, accumulation of senescent endothelial cells and endothelial-mesenchymal transition (EndoMT). In this review, we will explore these pathophysiological cascades and their interrelation with endothelial dysfunction. We will then present the scientific evidence to quercetin’s anti-atherosclerotic, anti-hypertensive, senolytic and anti-EndoMT effects. Finally, we will discuss the prospect for its clinical use in alleviating myocardial ischemic injuries in IHD.